(untitled) (Eurasian Journal of Research, Development and Innovation, 2024)
In recent years, there has been an increase in the prevalence of obesity among children and adolescents of different ages. This study surveyed children and adolescents with overweight and obesity to study their daily routine, physical activity and nutrition. As a result of the study, the main factors contributing to the development of obesity and the most common age of onset of obesity in respondents were identified.